2020
DOI: 10.1016/j.cegh.2020.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and projection of burden of cancer due to tobacco in India till 2025

Abstract: Background: For effective planning and optimum allocation of resources, accurate assessment of burden due to tobacco and its projection is essential. There are number of reports in India during last 3-4 decades, reporting tobacco related cancers (TRC). However, there is no visible study in India attempting to assess cancers due to tobacco (CDT). Objectives: To assess CDT in India and States by sex and urban/rural and project the same till 2025. Materials and methods: The basic inputs required were 1) tobacco p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Reported variations in HPV prevalence among cancer cases in India are due to different detection methods, population, geographic locations and sample size. However, major proportion could be attributed to tobacco use (59.0%) and consumption of alcohol (4.7%) [34,35]. Existing policies and programmes to prevent and control these risk factors should be reinforced to bring down cancer burden [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported variations in HPV prevalence among cancer cases in India are due to different detection methods, population, geographic locations and sample size. However, major proportion could be attributed to tobacco use (59.0%) and consumption of alcohol (4.7%) [34,35]. Existing policies and programmes to prevent and control these risk factors should be reinforced to bring down cancer burden [36].…”
Section: Discussionmentioning
confidence: 99%
“…Globally in 2018, human papillomavirus (HPV) accounted for 31% cancer cases amongst 13% of all human infection related incident cancer cases [1]. HPV types 16,18,26,31,33,35,39,45,51,52,53,56,58,59, 66, 68, 73 and 82 are classified as carcinogenic to humans [2]. Persistent HPV infection (especially HPV types 16 and 18) is known to cause the cervical cancers and a significant proportion of the anogenital and head and neck cancers [3].…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that in states namely Manipur, Mizoram, Tripura, Meghalaya, and Assam the number of cancer cases due to tobacco is around 60 percent of other respective states. 1 A study conducted by B. Barooah Cancer Institute (BBCI) reported cancer statistics in Kamrup Urban District, including incidence and mortality, revealed the statistics of remarkable growth of cancer cases in Assam. The number of new cases of all cancer was increased from 155.3 to 188.5 and 102.7 to 165.3 per 100,000 men and women respectively from the year 2007 to 2011.…”
Section: Introductionmentioning
confidence: 99%